Introducing a Professional Development Skill Building Platform Into a Biomedical Sciences Graduate Program Curriculum in Pharmacology - Elizabeth S. Yeh; Jennelle D. Richardson (Pharmacology Research & Perspectives)
ABSTRACT Biomedical graduate students are training for diverse careers that extend beyond the academic environment. However, many graduate programs are designed to train individuals in a specialized scientific field, and the main research project of trainees is often narrow in scope, with a focus on a specific topic of intense study. To be effective in the scientific workforce, trainees need skills beyond what is learned through bench science and critical thinking that supports scientific discovery. Generalizing critical thinking to improve interpersonal interactions through communication, emotional intelligence, and an understanding of the environment in shaping career development is similarly crucial for professional success. To prepare trainees beyond the typical focused scientific project and training, this manuscript describes the process and outcomes for a graduate program in pharmacology that piloted a course containing intentionally designed curriculum to reach beyond the traditional scope of training and provide skills‐based professional and career development training. Here, we share the course design, feedback from students across 5 years, and lessons learned about implementing this type of strategy. Each year, students were provided short voluntary surveys to complete, and the surveys were used to determine whether students thought the material was relevant and helped them to be better scientists. The surveys were also used to create the course syllabus each semester in a semi‐on‐demand fashion. Overall, data suggest that the students perceived that the course is beneficial and that it is challenging to address all needs at all times.